Implementasi Teori Belajar Humanisme dalam Pembelajaran Pendidikan Agama Islam Perspektif Carl Rogers - Arofaturrohman, Yunita Azmil; Alqudsi, Zainab; Fauziati, Endang (Lembaga Yasin AlSys, 2023)
Learning humanism is important to apply in every educational institution, the purpose of this education is to humanize humans and has the task of educating, nurturing and guiding children to become whole human beings, behavior, morality, ethics and knowledge. This study aims to describe the implementation of humanism learning theory in learning Islamic Religious Education Carl Rogers Perspective. The type of research used is descriptive qualitative with the library research method, namely library research. Research data obtained from the recording of books and journals. Learning Islamic Religious Education in relation to the theory of humanism can be applied through the study of monotheism, jurisprudence and morals. The application of humanistic theory to the learning of Islamic Religious Education can be done by incorporating it through learning planning. Educators need to pay attention to the character and experiences of each student, because each student certainly has different characters and experiences.